Zagadnienie pomocy publicznej udzielanej na ochronę środowiska – teoria zawodności rynku a polityka konkurencji Unii Europejskiej - Podsiadło, Piotr (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The aim of this article is to present the conditions of admissibility of state aidin the European Union, with particular emphasis on horizontal aid for environmentalprotection. State aid measures can correct market failures and therebycontribute towards achieving common objectives. It should be targeted towardssituations where aid can bring a material improvement that the market cannotdeliver alone. The EU Member States intending to grant environmental or energyaid have to define precisely the objective pursued and explain what is the expectedcontribution of the measure towards this objective.